2015
DOI: 10.1016/j.jsat.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Prior Experience with Non-Prescribed Buprenorphine: Role in Treatment Entry and Retention

Abstract: Buprenorphine availability continues to expand as an effective treatment for opioid dependence, but increases in availability have also been accompanied by increases in non-prescribed use of the medication. Utilizing data from a randomized clinical trial, this mixed-method study examines associations between use of non-prescribed buprenorphine and subsequent treatment entry and retention. Quantitative analyses (N=300 African American buprenorphine patients) found that patients with prior use of non-prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Increased experience with buprenorphine or the clinic may improve future treatment retention and success. (Cunningham et al, 2013; Monico et al, 2015) This observation suggests the need for better outreach through measures such as telephone-based recovery assistance programs or harm reduction programs to encourage and facilitate treatment re-entry. (Proctor, Wainwright, Herschman, & Kopak, 2017; Shah, BS, Sohler, PhD, MPH, López, BA, Fox, MD, & Cunningham, MD, MS, 2013) Such outreach may ultimately benefit patients by reducing mortality and morbidity associated with being out of treatment.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Increased experience with buprenorphine or the clinic may improve future treatment retention and success. (Cunningham et al, 2013; Monico et al, 2015) This observation suggests the need for better outreach through measures such as telephone-based recovery assistance programs or harm reduction programs to encourage and facilitate treatment re-entry. (Proctor, Wainwright, Herschman, & Kopak, 2017; Shah, BS, Sohler, PhD, MPH, López, BA, Fox, MD, & Cunningham, MD, MS, 2013) Such outreach may ultimately benefit patients by reducing mortality and morbidity associated with being out of treatment.…”
Section: 0 Discussionmentioning
confidence: 99%
“…As outlined in Table 3 . Similarly, three of the six buprenorphine cohorts reported significant effects, with cocaine associated with reduced retention [56,58,71]. A smaller number of studies reported significant effects for benzodiazepines; two [75,76] of the six MMT cohorts reported illicit benzodiazepine use was associated with reduced retention.…”
Section: Plos Onementioning
confidence: 96%
“…The majority of the observational studies involved a retrospective cohort study design (n = 37) PLOS ONE [37, 39, 42-44, 46, 49-54, 58, 59, 63, 64, 68-70, 72-74, 76, 79-82, 84-87, 89-91, 93, 94, 97], with prospective cohort studies accounting for a further 23 studies [35, 36, 38, 40, 41, 45, 47, 48, 55, 57, 60-62, 65-67, 75, 77, 78, 83, 87, 88, 97]. The remaining three studies involved an ambidirectional cohort study [95] and analyses of data collected as part of an RCT [56,71].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey results from smaller samples of people seeking or receiving OUD treatment were consistent with these larger samples, with reports of buprenorphine misuse more frequent than for abuse. A qualitative study of 20 adults being admitted into a buprenorphine-based MAT program reported 75% had used non-prescribed buprenorphine prior to starting MAT (Monico et al, 2015). The authors concluded that the primary motive for misuse was to prevent the onset of opioid withdrawal, since "none of the respondents mentioned seeking or using buprenorphine with the intention of 'getting high' and, in fact, made a clear distinction between seeking heroin to 'get high' and seeking buprenorphine to stop 'physical pain,' 'not be sick that day,' or 'hold' them until they were able to acquire quality heroin.…”
Section: Individuals Seeking or Receiving Oud Treatmentmentioning
confidence: 99%